2023
DOI: 10.1111/1750-3841.16468
|View full text |Cite
|
Sign up to set email alerts
|

Sequential culture with aroma‐producing yeast strains to improve the quality of Kyoho wine

Abstract: Despite many non-Saccharomyces yeasts being considered spoilage microorganisms, they can increase aroma and flavor diversity in alcoholic beverages. The purpose of this study was to investigate nontraditional inoculation strategies using aroma-producing yeast strains for Kyoho wine fermentation, followed by an instrumental analysis and sensory evaluation. The winemaking process was carried out using Saccharomyces cerevisiae Gr112, Hanseniaspora uvarum Pi235, and Pichia kluyveri Pe114. Multiple inoculation stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The aroma-producing yeast was widely used during the production of traditional fermented foods, such as wine [ 54 ], Baijiu [ 55 ], and soy sauce [ 56 ]. CM15 that showed both the stronger ability to utilize substrates to produce esters and the excellent tolerance to industrially relevant stress factors could improve the quality of rice-flavor Baijiu, which might be also appropriate to be used as the potential functional microorganism to improve the quality of some other fermented foods.…”
Section: Discussionmentioning
confidence: 99%
“…The aroma-producing yeast was widely used during the production of traditional fermented foods, such as wine [ 54 ], Baijiu [ 55 ], and soy sauce [ 56 ]. CM15 that showed both the stronger ability to utilize substrates to produce esters and the excellent tolerance to industrially relevant stress factors could improve the quality of rice-flavor Baijiu, which might be also appropriate to be used as the potential functional microorganism to improve the quality of some other fermented foods.…”
Section: Discussionmentioning
confidence: 99%
“…The aroma profile and overall quality of fruit wine could be enhanced by using non‐ Saccharomyces yeast which secrete specific extracellular enzymes, such as proteases, pectinases, cellulases, glucosidases and lipid hydrolases, which act on the relevant substrates in fruit juice to produce alcohols, esters, acids, terpenes and other substances (Chen et al ., 2021; Sun et al ., 2022; Lai et al ., 2023a). Research has shown that cofermentation with multiple yeasts enhances the quality of fruit wine through synergistic interactions (Lai et al ., 2023b). Furthermore, different inoculation techniques (pure, simultaneous and sequential) could also play a significant role in producing fruit wine with distinct characteristics (Kapsopoulou et al ., 2007; Bely et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, application of single yeast in fruit wine fermentation could potentially lead to incomplete breakdown of complex substrate, resulting in poor‐quality (Wang et al ., 2016). The aroma profile and overall quality of fruit wine could be enhanced by using non‐ Saccharomyces yeast which secrete specific extracellular enzymes, such as proteases, pectinases, cellulases, glucosidases and lipid hydrolases, which act on the relevant substrates in fruit juice to produce alcohols, esters, acids, terpenes and other substances (Chen et al ., 2021; Sun et al ., 2022; Lai et al ., 2023a). Research has shown that cofermentation with multiple yeasts enhances the quality of fruit wine through synergistic interactions (Lai et al ., 2023b).…”
Section: Introductionmentioning
confidence: 99%